#### Answer

$$x = 12$$
To check if we have the correct solution, let us plug $12$ into the original equation for $x$. If both sides of the equation equal one another, then the solution is correct:
$$0.05[(7(12) + 36] = 0.4(12) + 1.2$$
Let's evaluate what is inside the parentheses first. Multiply within the parentheses first, according to order of operations:
$$0.05(84 + 36) = 0.4(12) + 1.2$$
Now, we add what is within the parentheses:
$$0.05(120) = 0.4(12) + 1.2$$
Multiply first:
$$6 = 4.8 + 1.2$$
Finally, we can add the terms on the right hand side:
$$6 = 6$$
Both sides of the equation are equal, so we know our solution is correct.

#### Work Step by Step

To solve this equation, we work step-by-step to isolate the variable on one side and the constant on the other. To do this, we use the order of operations, represented by the acronym PEMDAS. This means that we evaluate parentheses first, then exponents and radicals, then multiplication and division, and, finally, addition and subtraction.
In this problem, we use distributive property first to get rid of all the parentheses:
$$0.05(7x) + 0.05(36) = 0.4x + 1.2$$
We now multiply out the terms:
$$0.35x + 1.8 = 0.4x + 1.2$$
Subtract $0.35x$ from both sides of the equation to isolate the variable to one side of the equation:
$$1.8 = 0.05x + 1.2$$
Subtract $1.2$ from both sides of the equation to isolate the constants to the other side of the equation:
$$0.6 = 0.05x$$
Divide both sides of the equation by $0.05$ to solve for $x$:
$$x = 12$$
To check if we have the correct solution, let us plug $12$ into the original equation for $x$. If both sides of the equation equal one another, then the solution is correct:
$$0.05[(7(12) + 36] = 0.4(12) + 1.2$$
Let's evaluate what is inside the parentheses first. Multiply within the parentheses first, according to order of operations:
$$0.05(84 + 36) = 0.4(12) + 1.2$$
Now, we add what is within the parentheses:
$$0.05(120) = 0.4(12) + 1.2$$
Multiply first:
$$6 = 4.8 + 1.2$$
Finally, we can add the terms on the right hand side:
$$6 = 6$$
Both sides of the equation are equal, so we know our solution is correct.